ANALISIS PERUBAHAN PENGGUNAAN LAHAN UNTUK EVALUASI KEJADIAN BANJIR DI KOTA MANADO - Helena Sri Sulastriningsih; Murni Sulistyaningsih; Irfan Rifani; Muhamad Isa Ramadhan (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
This study aims to evaluate land-use changes in the city of Manado against the occurrence of floods in 2021. Analysis of land-use changes was carried out using the overlay method on maps in 2013 and 2020 with the help of GIS. The runoff coefficient value is obtained based on the land use approach by using the runoff coefficient value table to determine the relationship between land use and runoff. The results of the study show that in the period 2013–2020 there have been changes in land use that disrupt hydrological functions. Forest land, mixed gardens, and shrubs decreased by 529.83 ha (3.48%), and conversely built-up land and open land increased by 124.14 ha (0.83%) which triggered an increase in surface runoff causing flooding. The increasing fulfillment of living needs along with population growth of 34,339 people (8.18%) in 7 years requires additional land for settlement, agriculture, and supporting infrastructure. Land-use change weakens hydrological functions and contributes to increased runoff. 17% of the rainfall in 2013 and 18% in 2020 will be a runoff. Rainfall in January 2014 and January 2021 was classified as very high (>500 mm). It can be stated that the flash floods that occurred in Manado in January 2014 and 2021 were triggered by land use and high rainfall factors.